2021
DOI: 10.1016/j.sjbs.2021.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of non-Streptococcus mutans bacteria in dental biofilm and its relation to caries progression

Abstract: This study aims to assess differences in biofilm bacterial composition between patients with low and high caries. Patients without a medical problem and with no history of antibiotic use, mouth wash or fluoride application in the previous 3 months were recruited. Caries was recorded at cavitation level; score was calculated by a national mean (dmft of 4.8 and DMFT of 2.7). Pooled biofilm samples were collected from mesial, distal, buccal, lingual, and occlusal surfaces. Based on caries experience, individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
15
2
Order By: Relevance
“…Further Spearman correlation analysis substantiated the significant negative correlation between Fusobacterium and Neocosmospora , indicating their opposite effects in maintaining CF condition or developing caries. In addition, although a number of studies have verified the promoting effects of S. mutans in ECC progression ( Momeni et al., 2020 ; Xiao et al., 2020 ; Baker et al., 2021 ), Streptococcus was found to be a characteristic in the CF sample and, meanwhile, negatively related to carious indexes in the present study, indicating the complicated roles that the Streptococcus species played in caries risk, and the intricate prevalence of Streptococcus species has also been reported by AlEraky et al. (2021) .…”
Section: Discussioncontrasting
confidence: 57%
“…Further Spearman correlation analysis substantiated the significant negative correlation between Fusobacterium and Neocosmospora , indicating their opposite effects in maintaining CF condition or developing caries. In addition, although a number of studies have verified the promoting effects of S. mutans in ECC progression ( Momeni et al., 2020 ; Xiao et al., 2020 ; Baker et al., 2021 ), Streptococcus was found to be a characteristic in the CF sample and, meanwhile, negatively related to carious indexes in the present study, indicating the complicated roles that the Streptococcus species played in caries risk, and the intricate prevalence of Streptococcus species has also been reported by AlEraky et al. (2021) .…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies showed that Streptococcus sanguinis ( S. sanguinis ) may play an antagonistic role against S. mutans colonization and is usually associated with tooth surfaces free of caries [ 43–45 ]. However, recently, Al Eraky DM et al reported that S. mutans was insignificant contributor to caries among Saudi patients, with caries mostly caused by S. sanguinis [ 46 ]. Here, significant decreases in the abundance of these species were observed in the DF group, consistent with a lower risk of future caries development.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent fndings prove otherwise. A study by AlEraky et al [18] showed that S. sanguinis has been identifed in patients with high levels of caries. Another study by Meriç et al [19] reported similar frequencies of S. mutans and S. sanguinis in groups of caries-and cariesfree subjects.…”
Section: Introductionmentioning
confidence: 99%